The Association Between Genetic Polymorphisms of Transporter Genes and Prognosis of Platinum-Based Chemotherapy in Lung Cancer Patients - He J; Wang Z; Zou T; Wang Y; Li XP; Chen J (Dove Medical Press, 2022)
Jia He,1,2 Zhan Wang,3 Ting Zou,4 Ying Wang,5 Xiang-Ping Li,1,2 Juan Chen1,2 1Department of Pharmacy, Xiangya Hospital, Central South University, Changsha, 410008, People's Republic of China; 2National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People's Republic of China; 3Department of Medical Oncology, Lung Cancer and Gastrointestinal Unit, Hunan Cancer Hospital, Affiliated Cancer Hospital of Xiangya School of Medicine, Changsha, 410013, People's Republic of China; 4National Institution of Drug Clinical Trial, Xiangya Hospital, Central South University, Changsha, 410008, People's Republic of China; 5Hunan clinical Research Center in Gynecologic Cancer, Hunan Cancer Hospital, Affiliated Cancer Hospital of Xiangya School of Medicine, Changsha, 410013, People's Republic of ChinaCorrespondence: Juan Chen, Department of Pharmacy, Xiangya Hospital, Central South University, Changsha, 410008, People's Republic of China, Tel +86-731-89753491, Email cj1028@csu.edu.cnObjective: Platinum-based chemotherapy is the first-line treatment of lung cancer. However, different individual and genetic variation effect therapy for lung cancer. The purpose of this study was to evaluate the association between transport genes genetic polymorphisms and the prognosis of platinum-based chemotherapy in lung cancer patients.Methods: A series of 593 patients with treatment of platinum-based chemotherapy were recruited for this study. A total of 21 single-nucleotide polymorphisms in nine transporter genes were selected to investigate their associations with platinum-based chemotherapy prognosis.Results: Patients with ABCG2 rs1448784 CC genotype had a significantly shorter PFS than CT or TT genotypes (Additive model: HR = 1.54, 95% CI = 1.02- 2.35, P = 0.040). In stratification analysis, SLC22A2 rs316003, SLC2A1 rs4658 were related to PFS and AQP9 rs1867380, SLC2A1 rs3820589, SLC22A2 rs316003 indicated were related to OS of platinum-based chemotherapy prognosis.Conclusion: Genetic polymorphisms of rs1448784 in ABCG2 might be potential clinical marker for predicting the prognosis of lung cancer patients treated with platinum-based chemotherapy.Keywords: lung cancer, platinum-based chemotherapy, prognosis, transporter gene, single nucleotide polymorphisms, SNPs